Profesjonalna społeczność ucząca się jako kontekst rozwoju zawodowego nauczycieli - Magrafta , Galit (Studia Edukacyjne, 2020)
The article presents the importance of the professional learning community in the school framework. It discusses the creation of a learning community, its characteristics, advantages, and the challenges in the leadership and establishment of a professional learning community. In addition, the article presents the importance of the introduction of a learning community into educational frameworks and provides a solution to the resources that pertain to the time or systemic flexibility.This article highlights the importance of collaborations, peer learning, and a productive discourse among teacher colleague